2018
DOI: 10.1088/1361-6552/aaa93a
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Arduino to study buoyancy force

Abstract: The study of buoyancy becomes very interesting when we measure the apparent weight of the body and the liquid vessel weight. In this paper, we propose an experimental apparatus that measures both the forces mentioned before as a function of the depth that a cylinder is sunk into the water. It is done using two load cells connected to an Arduino. With this experiment, the student can verify Archimedes' principle, Newton's third law, and calculate the density of a liquid. This apparatus can be used in fluid phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
8
0
2
Order By: Relevance
“…The model which was an object representation of physical phenomena in this study was an Arduino and sensor devices. Other physics concepts can be studied using Arduino (Espindola, Cena, Alves, Bozano, & Goncalves, 2018;La Rocca, Riggi, & Pinto, 2020). Models and representations are considered as necessary tools for reasoning (Kind & Osborne, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The model which was an object representation of physical phenomena in this study was an Arduino and sensor devices. Other physics concepts can be studied using Arduino (Espindola, Cena, Alves, Bozano, & Goncalves, 2018;La Rocca, Riggi, & Pinto, 2020). Models and representations are considered as necessary tools for reasoning (Kind & Osborne, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Pedagogically, the study confirmed that combining theory with practical activities helps in the teaching and learning processes, as the student is no longer a mere spectator e-ISSN nº 2447-4266 Palmas, v. 7, n. 2, p. 1-19, abr.-jun., 2021Palmas, v. 7, n. 2, p. 1-19, abr.-jun., http://dx.doi.org/10.20873/uft.2447 14 of lectures and, when challenged to solve the proposed problems, accessed prior knowledge, reflected on the possible results, defined paths to reach the results, accessed theoretical knowledge to solve practical activities, building and giving meaning to the assimilated knowledge. Espindola et al (2018) studied the apparent weight of bodies, proposing an experimental apparatus that measures the resulting force exerted by the fluid on a body, as a function of the depth inside a cylinder with water. In this experiment, we chose to use the Arduino microcontroller for automatic data collection.…”
Section: Nascimento Et Al (mentioning
confidence: 99%
“…It also demonstrated that the experimental apparatus can be used in physics laboratories replacing commercial kits, as the limitations regarding accuracy are irrelevant when compared to the countless possibilities of student learning (ESPINDOLA et al, 2018). Atkin (2018) studied the flow of liquid inside a container with a drainage hole under the action of gravity, based on Torricelli's theorem.…”
Section: Nascimento Et Al (mentioning
confidence: 99%
“…Pedagogicamente, o estudo confirmou que aliar a teoria às atividades práticas auxilia nos processos de ensino e de aprendizagem, pois o estudante deixou de ser mero expectador das aulas expositivas e, ao ser desafiado a resolver os problemas propostos, acessou conhecimentos prévios, refletiu sobre os possíveis resultados, definiu caminhos para chegar aos resultados, acessou conhecimentos teóricos para resolver atividades práticas, construindo e dando significado ao conhecimento assimilado. Espindola et al (2018) estudaram o peso aparente dos corpos, propondo um aparato experimental que media a força resultante exercida pelo fluido sobre um corpo, em função da profundidade dentro de um cilindro com água. Neste experimento optouse pelo uso do microcontrolador Arduino para a obtenção automática dos dados.…”
Section: Atkin (2018)unclassified
“…De acordo com a pesquisa, o experimento proporcionou ao estudante uma melhor compreensão do princípio de Arquimedes, da terceira lei de Newton e da densidade de um líquido. Demonstrou também que o aparato experimental pode ser usado em laboratórios de Física substituindo os kits comerciais, já que as limitações quanto à precisão são irrelevantes quando comparadas com as inúmeras possibilidades de aprendizagem do estudante (ESPINDOLA et al, 2018). Atkin (2018) estudou o fluxo de líquido dentro de um recipiente com orifício de drenagem sob a ação da gravidade, baseado no teorema de Torricelli.…”
Section: Atkin (2018)unclassified